Bistatic SAR for Building Wall Material Characterisation - Elgy, James (Cranfield University, 2020)
This thesis addresses the problem of using radar to extract interpretable information concerning both the structure and electrical properties of a wall, and the environment behind it. This is broken down into two subproblems: how to determine the thickness and electromagnetic properties of the wall without being in direct contact with it, and how to obtain the most accurate images of what lies beyond the wall. Existing research in the area is evaluated and a theoretical study is presented on the use of monostatic, bistatic, and multistatic Synthetic Aperture Radar (SAR) in both one and two dimensional apertures. New methods of determining the wall properties are evaluated by both computer simulation and with laboratory radar measurements, where a wall of concrete blocks is constructed. The robustness of the asymmetric SAR geometry approach is evaluated with the addition of complex objects placed behind the wall. The uncertainty associated with estimating the wall properties is evaluated and consequential improvements to image quality are discussed. It was found that an asymmetric bistatic SAR geometry accurately extracts the refractive index and thickness of a wall. The method is applicable to both cluttered environments and non-parallel wall trajectories without loss of accuracy. Applying a compensation for refraction in the SAR imagery results in better positional accuracy but does not necessarily result in better image focusing. Volumetric multistatic image formation benefits from applied refraction compensation. SAR image formation, and in particular volumetric image formation, can be significantly accelerated via a spatially variant basebanding technique followed by zero padding. Spatially variant basebanding is sub optimal when applied to a Through-Wall radar scenario where there is a visible wall signature in the image. Keywords: Through-Wall radar, Multistatic radar, Multidimensional signal processing, Electromagnetic propagation, Radar imagin
© Cranfield University 2020. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Through-Wall radar; Multistatic radar; Multidimensional signal processing; Electromagnetic propagation; Radar imaging